Analisis Permintaan Uang dan Penawaran Uang serta Implikasinya Terhadap Kebijakan Moneter - Angin, Sutejo Perangin; Ruslan, Dede; Pratomo, Wahyu Ario (Jurnal Samudra Ekonomi dan Bisnis, 2025)
Bank Indonesia sets the main objectives of monetary policy to achieve stability in the value of the rupiah, maintain payment system stability, and maintain financial system stability, in order to support economic growth. The aim of this research is to analyze the influence of GDP on the demand for money, the influence of the BI-Rate on both the demand for money and the supply of money, as well as the influence of inflation, the exchange rate and the statutory reserve requirement (GWM) on the supply of money, and the implications for monetary policy. Research period 2010-2023. The data analysis method is the Two Stage Least Square (2SLS) simultaneous equation model. The results obtained are that GDP has a significant positive effect on the demand for money, BI-Rate has a significant negative effect on both the demand for money and the supply of money, inflation has a significant negative effect on the supply of money, and the exchange rate and GWM are proven to have a significant positive effect on the supply of money.